In Situ Gelling Dexamethasone Oromucosal Formulation: Physical Characteristics Influencing Drug Delivery - Daniel Krchňák; Ľudmila Balážová; Michal Hanko; Dominika Žigrayová; Miroslava Špaglová (Gels)
The study focuses on the development of an in situ gelling dexamethasone (DEX) oromucosal formulation designed for the treatment of aphthous stomatitis. Three series of formulations were prepared; a first series containing DEX suspended, a second series containing DEX and, in addition, mint essential oil (EO), and a third series containing EO and DEX solubilized in propylene glycol (PG). In the composition, polymers in the role of mucoadhesive agent were interchanged (hydroxypropyl methylcellulose (HPMC), hydroxypropyl cellulose (HPC), hydroxyethyl cellulose (HEC), methyl cellulose (MC), carboxymethyl cellulose (CMC), and sodium carboxymethyl cellulose (NaCMC). Specifically, DEX was incorporated at a concentration of 0.1% (w/w) in each formulation. The influence of mint EO and DEX solubilization on the physical properties (pH measurements, rheological analysis, swelling ability, and texture analysis) and in vitro drug release was studied. Key findings revealed that HPMC-based formulation containing mint EO and PG exhibited best swelling properties (700 ± 46% after 5 h), adequate adhesiveness and in vitro drug release (34.7 ± 5.9%). Furthermore, the irritation potential assessed via the hen’s egg test on the chorioallantoic membrane (HET-CAM) demonstrated low irritancy risk. Finally, Fourier-transform infrared spectroscopy (FT-IR) showed no incompatibility between DEX and excipients. Overall, the research highlights the potential of mucoadhesive systems in improving the therapeutic efficacy of oromucosal drug delivery for managing painful oral lesions.